Influence of Duck Eggshell Nano-Calcium Fortification on the Chemical Quality of Beef Sausage - Agus Hadi Prayitno; Dyah Laksito Rukmi; Agatha Widiyawati; Budi Prasetyo (Jurnal Ilmu Ternak dan Veteriner, 2022)
Duck eggshells are one of bio-wastes from poultry industry and household  that have been disposed. Duck eggshells contain high calcium which can be applied as an alternative source of daily calcium for the body. Nanostructured duck eggshell calcium can be used as a food additive in beef sausage processing. This study was conducted to determine the chemical quality of beef sausage fortified by duck eggshell nano-calcium. The materials include beef, soy protein isolate, palm oil, garlic, salt, pepper, shallot, onion, tapioca, monosodium glutamate, sodium tripolyphosphate, nutmeg, coriander, frankfurter, sugar, duck eggshell nano-calcium, ice, and nano-structured duck eggshell. Treatments for fortification of duck eggshell nano-calcium were 0; 0.15; 0.3; 0.45; and 0.6% of the total dough. Parameters tested were moisture, protein, fat, carbohydrate, fiber, ash, sugar, calcium, sodium, and energy of the sausage. Each treatment consisted of 5 replications. Data collected was analyzed by analysis of variance using completely randomized design and if there was significant different (P0.01) then further tested by the Duncan's New Multiple Range Test. Results showed that the fortification of duck eggshell nano-calcium had a highly significant effect (P0.01) on protein, fat, ash, sugar, calcium, and sodium, but did not affect moisture, carbohydrate, fiber, and energy of beef sausage. Fortification of duck eggshell nano-calcium up to 0.6%  increased protein, ash, dan calcium but decreased fat, sugar, and sodium of beef sausage.